Multilingualism in Sunan Ampel Tomb Complex: A Linguistic Landscape Study - Kartika Nuswantara; Hurrotul Firdausiyah; Zuliati Rohmah; Diana Nur Sholihah (Insaniyat : Journal of Islam and Humanities, 2021)
The present study focuses on the languages operating on the written signage that contribute directly to theformation of the linguistic landscape. The study chose Sunan Ampel Tomb in Surabaya, Indonesia, as one ofthe sites that has become a heritage conservation due to the history hidden in the site. This site is a part of the other sites in a series leading to the history of nine saints (Wali Songo) who brought Islam to Indonesia through one of the islands, Java. The study aimed at describing the linguistic landscape of the site to help learn about the languages operating on the signage found in Sunan Ampel Tomb complex and the hidden history leading to multilingual multilingualism in the area. By using a direct observation and interview to gather the data,the study informs that the sites are typically dominated with Indonesian language operating in monolingualsignage. Despite a few in number, the multilingual signage can still be found to depict several languages including English, Arabic, and Indonesian language. The domination of Bahasa Indonesian demonstrates the implementation of policy for using the language as the national language. While English and Arabic are used for the business purpose. The study also discovers the characteristics of the language displaying on the signage from the size of the fonts. In conclusion, linguistic landscape in Sunan Ampel Tomb describes the history of how the saint brought Islam to the society. Arabic artifacts stereotyping Islam existence can hardly be found here, and it becomes a proof the saint taught Islam without trying to change the already existing customs, cultures, and languages as well.